2020
DOI: 10.1108/nfs-02-2020-0039
|View full text |Cite
|
Sign up to set email alerts
|

Food packaging design and consumer perception of the product quality, safety, healthiness and preference

Abstract: Purpose The purpose of this paper is to assess the impact of the packaging design on consumers’ perception of the food quality, safety, healthiness and preference to buy. Design/methodology/approach A cross-sectional study recruited a convenience sample of 547 Lebanese adults with a median age of 30 years old and 54% being females, between November and December 2016, using an interviewer-based questionnaire. Findings As identified by the participants, packaging should “protect the food” (54.9%) and be safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
1
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 42 publications
0
17
1
2
Order By: Relevance
“…This was an unexpected result, contrary to our initial hypothesis, as we believed that diabetics/pre-diabetics could be more careful with claims, avoiding consuming sugary products. Our results contrast with previous published studies, which showed that older people, those with high BMI (Bou-Mitri et al, 2020b) and those that are following specific diets (Bou-Mitri et al, 2020a) pay more attention to the health claims included in the food package. The highest misunderstand levels were observed for the claims "containing sugars from own ingredients" and "light on sugar."…”
Section: Discussioncontrasting
confidence: 99%
“…This was an unexpected result, contrary to our initial hypothesis, as we believed that diabetics/pre-diabetics could be more careful with claims, avoiding consuming sugary products. Our results contrast with previous published studies, which showed that older people, those with high BMI (Bou-Mitri et al, 2020b) and those that are following specific diets (Bou-Mitri et al, 2020a) pay more attention to the health claims included in the food package. The highest misunderstand levels were observed for the claims "containing sugars from own ingredients" and "light on sugar."…”
Section: Discussioncontrasting
confidence: 99%
“…In addition to its traditional role, packaging also serves as a communication and branding medium. As a marketing tool, it allows to promote a healthier lifestyle and thus influences the change of consumer habits [294,295]. However, it has been shown that the cost of producing bio-packaging from residues can be up to three to five times more expensive compared to packaging made of fossil-based materials [296].…”
Section: Economic Effects Of Using Edible Polysaccharide Films and Coatingsmentioning
confidence: 99%
“…The packaging is one of the most powerful tools in food industry as it acts also as a communication and branding medium beside its traditional role. As a marketing tool the packaging can promote a healthier lifestyle and change by itself the consumer habits [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%